Increasing Awareness of the Indonesian Archipelago Through the Implementation of Community Service in International Cooperation with Rajamangala University, Thailand: Meningkatkan Kesadaran Wawasan Nusantara Melalui Implementasi Pengabdian Masyarakat Kerjasama Internasional dengan Universitas Rajamangala Thailand - Andini Khoirunnisa; Hidayat, Sarip; Bias Lintang Dialog; Ms. Sineenat Suasungnern; Erga Yuhandra; Suwari Akhmaddhian; Dikha Anugrah; Haris Budiman; Yani Andriyani; Iman Jalaludin Rifa’i (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
Foreign culture entering Indonesia can have positive or negative impacts. Negative influences are mainly caused by the public's attitude towards foreign culture, which does not sort or filter it, which will unconsciously eliminate Indonesian identity. The purpose of this International Community Service is to strengthen the Nusantara insight and publicize it to the international world. The Implementation Method used consists of 3 (three) stages, namely the Audience, Implementation and Evaluation stages. The Results and Discussion that the Nusantara insight must be mastered, upheld and applied in everyday life. The conclusion is that the Nusantara Insight must be publicized to the international world through international community service or through collaboration in research so that it can be used as a basis for Indonesian citizens to have character and identity that is inherent in their society. Suggestions for the socialization of the Nusantara Insight need to be carried out systematically so that the younger generation from various countries in the world understands and comprehends Indonesia's position.